Identifikasi Serangga Predator pada Refugia Tembelekan (Lantana camara) Liar dan Hybrid di Universitas Sriwijaya - Diyanah, Syarifah; Saniyyah, DR; Oktari, F; Arnila, N; Adawiyah, R; Syahfira, RI; Simarmata, V (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Syarifah D, Saniyyah DR, Oktari F, Arnila N, Adawiyah R, Syahfira RI, Simarmata V. 2022. Identification of predatory insect in wild and hybrid tembelekan (Lantana camara) refugia at Sriwijaya University. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 403-413. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Refugia plants have several benefits, including as a system mechanism that includes improving the availability of alternative foods such as pollen, nectar, and honeydew, shelters used by predatory insects to survive through changing seasons or shelter from environmental extremity factors or pesticides, and provide habitat for alternative hosts or prey. This observation activity aimed to identify the types of predatory insects on hybrid cultivated tembelekan (Lantana camara) plants and those that grow wild that come or land on the refugia at Sriwijaya University. Observations were made by direct observation method, then identified using the google lens application and reviewed with a literature study of the predatory insects found. Then the data that has been obtained is calculated using the species diversity index using the Shannon-Weiner index formula and the species evenness index using the Pielou's index. The results showed that there were 4 orders of predatory insects found in wild refugia, namely Araneae, Diptera, Odonata, and Hymenoptera. Meanwhile, in the cultivated hybrid refugia, there were 3 orders of predatory insects, namely Hymnoptera, Diptera, and Araneae with the highest abundance of individual insects in the order Hymenoptera. The diversity index value of predatory insects on cultivated refugia tembelekan was 1.131 while the diversity index value of wild-growing Lantana camara was 1.167. The evenness index value of predatory insect species in hybrid tembelekan was 0.582, while the value of wild-growing Lantana camara was 0.600. Thus, the diversity value of predatory insects in both refugia showed a value of 1 < H'< 3 which is moderate, where the distribution of the number of individuals of each species or general was moderate and the stability of the community was moderate. Efforts to utilize wild and cultivated hybrid refugia can maximize the conservation function of predatory insects.